Analysis of Narrative Structure in the Short Story The Garden Party by Katherine Mansfield - , Sefrianus Rianto; I Ketut Suardana; Yoga Putra Semadi (Universitas Bali Dwipa, 2025)
This study aims to analyze the narrative structure in the short story The Garden Party by Katherine Mansfield, focusing on storytelling elements such as orientation, complication, resolution, and reorientation. The story portrays social inequality through the perspective of the main character, Laura, a young girl from an upper-class family who experiences an internal crisis when confronted with the harsh realities of working-class life. This study employs a qualitative approach with a grounded theory method to analyze the narrative structure in the short story The Garden Party by Katherine Mansfield. Data collection techniques include documentation, in-depth textual study, and content analysis of the literary work. The narrative structure theories of Vladimir Propp and Tzvetan Todorov are used to reveal how Mansfield constructs the plot and builds emotional tension as well as the character’s social awareness. The findings show that Mansfield effectively employs narrative structure techniques to create a psychological transformation in the protagonist while delivering a contextual social critique of the upper class's indifference toward the suffering of the lower class. This study contributes to modern literary studies and broadens readers’ understanding of storytelling techniques inmodern literature.